ETIKA DIGITAL ISLAMI SEBAGAI PONDASI MORAL GENERASI Z DI ERA TEKNOLOGI INFORMASI - Yanuar; Isryad Sabil; Darryl (Jurnal Serina Abdimas, 2026)
The development of digital technology in the era of the Industrial Revolution 4.0 has fundamentally transformed the social, cultural, and religious behavior of society, particularly among Generation Z. According to a report by the Ministry of Communication and Information (Kominfo, 2024), more than 85 percent of Indonesian adolescents are active on social media daily; however, most of them lack an adequate understanding of digital ethics and responsibility. This condition has led to various phenomena, such as the spread of misinformation, hate speech, and moral degradation, which negatively affect religious values and national character. This Community Service Program (Pengabdian kepada Masyarakat/PKM) aims to enhance the understanding and skills of youth at At-Taqwa Muhammadiyah Pejuang Mosque, Bekasi, in applying Islamic digital ethics based on the values of the Qur’an and Hadith. The program employed a participatory-educational approach through interactive lectures, training on Islamic content creation, and reflective simulations. The expected outcomes include increased ethical awareness, the formation of beneficial digital communities, and the emergence of an excellent and morally upright Generation Z in the digital space. The outputs of this program consist of a training module, a PKM scientific article, and positive social media publications grounded in the principles of faith (iman), trustworthiness (amanah), and excellence (ihsan). ABSTRAK Perkembangan teknologi digital di era Revolusi Industri 4.0 telah mengubah secara fundamental perilaku sosial, budaya, dan religius masyarakat, terutama di kalangan generasi Z. Berdasarkan laporan Kominfo (2024), lebih dari 85 persen remaja Indonesia aktif di media sosial setiap hari, namun sebagian besar belum memahami dimensi etika dan tanggung jawab digital. Akibatnya, muncul fenomena seperti penyebaran hoaks, ujaran kebencian, serta degradasi moral yang berdampak negatif pada citra keagamaan dan karakter bangsa. Kegiatan Pengabdian kepada Masyarakat (PKM) ini bertujuan meningkatkan pemahaman dan keterampilan remaja Masjid At-Taqwa Muhammadiyah Pejuang, Bekasi, dalam menerapkan etika digital Islami berbasis nilai Al-Qur’an dan Hadis. Metode pelaksanaan menggunakan pendekatan partisipatif-edukatif melalui ceramah interaktif, pelatihan pembuatan konten Islami, dan simulasi reflektif. Hasil yang diharapkan ialah meningkatnya kesadaran etis, terbentuknya komunitas digital berfaedah, serta lahirnya generasi Z yang unggul dan berakhlak mulia di ruang digital. Luaran kegiatan berupa modul pelatihan, artikel ilmiah PKM, dan publikasi media sosial positif berlandaskan prinsip iman, amanah, dan ihsan.